PRAGMALINGUISTIC STUDY OF INTERPERSONAL COMMUNICATION IN CONFLICTING COMMUNICATIVE SITUATIONS FROM A LINGUOCULTUROLOGICAL PERSPECTIVE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article scientifically analyzes the linguoculturological and pragmalinguistic features of interpersonal communication in conflict communicative situations. The study highlights how conflicts in communication between people from different cultural backgrounds are manifested through language units, speech acts, cultural connotations and communicative strategies. Also, the pragmatic goals of speakers in controversial situations, means of mitigating or intensifying the conflict, and the influence of socio-cultural values on the speech process are studied. The article interprets such elements as the emotional state of the communication participants, speech etiquette, metaphorical expressions, reproach, objection, and speech forms calling for compromise from a linguoculturological point of view. The results of the study serve to effectively manage conflict communication, enhance intercultural understanding, and develop communicative competence.